Is technological change really skills-biased? Firm-level evidence of the complementarities between ICT and workers' education - Thomas Bolli; Filippo Pusterla (ETH Zurich, KOF Swiss Economic Institute, 2019)
This paper extends and refines the concept of ICT-driven skills-biased technological change by disentangling the effects of information technologies (IT) and communication technologies (CT). Guided by the theory that IT and CT differently affect firms' production processes, we investigate the complementarities between these two distinct technologies and workers' levels of education in affecting firms' productivity. Exploiting within-firm variation between 2005-2017, we find that the use of IT measured as use of business management tools is particularly beneficial for workers with a tertiary vocational education. In contrast, CT measured as workers' use of the intranet is especially complementary to workers with a tertiary academic education. While consistent with the ICT-driven skills-biased technological change hypothesis, our results offer evidence on the necessity for differentiating between the effects of IT and CT on firm productivity when differently educated workers use these technologies.
hdl:20.500.11850/385031
Keywords: J24; O33; 330; skills-biased technological change; information technologies; communication technologies